Fertility and family income on the move: An international comparison over 20 Years - Nicola Dickmann (Luxembourg Income Study (LIS), 2003)
The income situation of families has always been a major topic for politicians and the public in modern welfare states. The ongoing call for better funding of families reflects the hardship of couples with children who seem to be unable to sustain the living standards of childless couples in similar circumstances. This study aims at providing some interesting facts about the correlation of fertility and income and on the income situation of families in order to provide a sound basis for further political discussions. It looks at the relative economic situation of families in comparison to childless couples so as to reveal incentive structures for couples to decide for or against children. Hereafter, investigations of different sources of family income try to clarify the reasons behind the observed developments over time. Furthermore, the often suggested correlation between low income and many children or high income and few descendants is being tested statistically in order to measure the relevance of the economic situation for the fertility decision. The paper is organised as follows: After explaining the methodological background of the selected sample and the calculation with the data of the Luxembourg Income Study (LIS), the study analyses the correlation between income and fertility. Next an investigation of the economic situation of families in comparison to childless couples at the very beginning of the 1980s is being conducted and compared with the data around 1990 and 2000. The paper then looks for explanation of the observed differences, first in comparing the cash benefits to families across countries over time followed by a closer look on the development of the personal income of family members. The paper ends with a brief discussion of the political implications of the findings.
Keywords: 330; Fertilität; Haushaltseinkommen; Familie; Vergleich; Soziale Lage; Deutschland; Großbritannien; USA; Finnland